CAREER GUIDANCE IN HIGHER EDUCATION: NEEDS AND PRACTICES - Oana GHEORGHE; Mirela ALEXANDRU (National Centre for Policy and Evaluation in Education, 2017)
The social development brings about ongoing transformation of the concept of "career", overcoming gender and cultural barriers. Career start may be difficult and the youth needs are dynamic. This makes the career counselling an area that continuously evolves and adjusts its strategies, methods and tools to the target group. This article analyses the connection between the career counselling services available at VIA College in Denmark and the specific needs of the students. We also wanted to draw attention upon the importance of developing career services, as these services can help students develop both their professional and transversal skills, enabling them to adapt more easily and faster to frequent changes of the labour market. The idea of creating a secure on-line platform to provide students with career counselling services can be taken up and adapted within the Romanian context.